The effect of PVC’s resin K-value on the mechanical properties of the artificial leather - Muh. Wahyu Syabani; Cynthia Devi; Indri Hermiyati; Andreas D Angkasa (Majalah Kulit, Karet, dan Plastik, 2019)
Artificial leather offer wide variety of application thus the demand is increased over time. The variation of the product needs different properties that can be achieved using resin with suitable k-value.This works reports the influence of the resin k-value on the mechanical properties of the artificial leather. The combination of various resin with different k-value (66, 68, 72, 74, and 76)is used and the tensile strength and elongation at break of the product were evaluated. The results show that blending the PVC resin with different k-value can be used to adjust the easier processing of the lower k-value and better mechanical properties of the higher k-value. Larger k-value differences between two resin make more difficulties of resin blending thus give more defect. For the blending of two resin, the tensile strength and elongation value would be between both of the resin initial properties. The final properties will be closer to the resin with a higher percentage in the resin blending.